Hydrogen-Rich Water Intake Accelerates Oral Palatal Wound Healing via Activation of the Nrf2/Antioxidant Defense Pathways in a Rat Model. (21st December 2015) - Tamaki, Naofumi; Orihuela-Campos, Rita Cristina; Fukui, Makoto; Ito, Hiro-O
Abstract : The wound healing process attempts to restore the integrity and function of the injured tissue. Additionally, proinflammatory cytokines, growth factors, and oxidative stress play important roles in wound healing. The aim of this study was to determine whether hydrogen-rich water intake induces the activation of the Nrf2/antioxidant defense pathway in rat palatal tissue, thereby reducing systemic oxidative stress and proinflammatory cytokine levels and promoting healing-associated genes. A circular excisional wound was created in the oral palatal region, and the wound healing process was observed. The rats were divided into two experimental groups in which either hydrogen-rich water or distilled water was consumed. In the drinking hydrogen-rich water, the palatal wound healing process was accelerated compared to that in the control group. As molecular hydrogen upregulated the Nrf2 pathway, systemic oxidative stresses were decreased by the activation of antioxidant activity. Furthermore, hydrogen-rich water intake reduced proinflammatory cytokine levels and promoted the expression of healing-associated factors in rat palatal tissue. In conclusion, hydrogen-rich water intake exhibited multiple beneficial effects through activation of the Nrf2/antioxidant defense pathway. The results of this study support the hypothesis that oral administration of hydrogen-rich water benefits the wound healing process by decreasing oxidative stress and inflammatory responses.